Bioconversion of Fermented Barley Waste by Black Soldier Fly Hermetia illucens L. (Diptera; Stratiomyidae) - Agus Dana Permana; Din Dzakamala Fafi Rohmatillah1; Ramadhani Eka Putra; Ucu Julita; Agus Susanto (Jurnal Biodjati, 2021)
Black Soldier Fly Larvae (BSFL), Hermetia illucens (Diptera: Stratiomyidae) are widely used as bioconverter agents for various organics waste, and BSF pupae are often used as fodder for poultry and fish, because the BSF pupae have a high protein content. This study focused on applying BSFL as a bioconversion agent of the fermented barley waste to convert it to larvae biomass. Prior to application, barley waste was fermented either using effective microorganisms-4 (EM4), leachate, and water for seven days. The fermented barley waste was applied as feeding material for BSFL at the rate of 100 mg/larvae/days. As control commercial chicken fed (CF) was applied as feeding material at a similar feeding rate. During this study, waste reduction index (WRI), and efficiency of digested feed (ECD) were calculated, and the protein content in the BSF prepupae was analyzed. The results of this study showed that BSFL fed with CF produces the shortest development time (27 days), and high consumption rate. BSFL fed with barley waste fermented with EM4 (BE) and Leachate (BL) produces a larval period of 31 and 30 days respectively, and statistically those were not significantly different from control. This study showed that treatments of BE and BL, produced a very high larval survival rates, 98.67% and 97.00% respectively, and those two treatments were not statistically different from the control (96.67%). Although the control treatment resulted in a higher WRI compared to the other treatments, but the ECD of BE and BL treatments were higher than the ECD of the control. From this study, it can be concluded that BSFL has a good ability to convert fermented barley waste as well as controls, and the prepupae has a high protein content (42%), so BSFL fed with fermented barley waste has the opportunity to be used as a fed for poultry and fish.